Identification of multiple rust resistant bread wheat genotypes - Khan, Hanif; Gangwar, Om Prakash; Bhardwaj, Subhash Chander; Prasad, Pramod; Parkash, Om; Mishra, Chandra Nath; Kumar, Raj; Krishnappa, Gopalareddy; Kumar, Satish; Yadav, Sonu Singh; Kashyap, Prem Lal; Kumar, Sudheer; et al. (Journal of Cereal Research, 2021)
A total of 320 advanced bread-wheat lines including some CIMMYT selections were screened at seedling stage against prevalent and virulent pathotypes of yellow, brown, and black rust pathogens. The Seedling Resistance Test (SRT) was performed under controlled environmental conditions (glasshouse) at IIWBR Regional Station Flowerdale, Shimla. Analysis of host-pathogen reaction revealed that 265 lines (82.8%) carried resistance against one or the other rust diseases. However, resistance to all three rust diseases was in 31 lines (9.7%). Important broad-spectrum rust-resistant genes such as Yr10, Yr15, Yr24, Lr24/Sr24, Lr42, Sr22, Sr26, Sr31, Lr34/Sr55/Yr18 inherited from their donor parents are likely resistance factor in many of the resistant genotypes.Â